Implementing Restorative Justice as an Alternative to Addressing Overcrowding in Prisons Bagan Siapi Api - Mulkanuddin Mulkanuddin; Risdalina Risdalina; Kusno Kusno (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Overcrowding is a pressing issue facing correctional institutions in Indonesia, including Bagan Siapi-api Prison. This situation impacts the quality of guidance, security, health, and the rights of inmates. Restorative justice, an approach that emphasizes restitution and peaceful conflict resolution through agreements between perpetrators, victims, and the community, offers an alternative that can reduce the burden of conventional criminal punishment. This study aims to analyze the implementation of restorative justice as an effort to reduce overcrowding in Bagan Siapi-api Prison. The research method uses a normative and empirical juridical approach. The results show that restorative justice can play a significant role in reducing the number of inmates, especially for minor crimes, although its implementation is still hampered by regulations, resources, and the understanding of law enforcement officials. Key challenges include the need for a shift in the mindset of law enforcement officials, strengthening regulations, providing trained facilitators, and ensuring a voluntary approach for victims. By addressing these challenges through multi-stakeholder commitment, restorative justice can be a transformative solution that not only eases the burden on prisons but also creates more meaningful justice and strengthens social cohesion in Rokan Hilir Regency.